The Internet of Things-based Smart Aquarium for Goldfish - Priyandoko, Gigih; Mukhsim, Mohamad; Subhan, M. Uhida; Fauzi, M. Lutfi (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2026)
Maintaining an ornamental fish aquarium requires continuous water quality monitoring and regular feeding management. However, manual monitoring is often inefficient and inconsistent, especially for users with limited time. Water temperature and pH are critical parameters that influence the health and survival of goldfish (Carassius auratus). This study proposes an Internet of Things (IoT)-based smart aquarium system that can automatically monitor and control water quality while providing scheduled feeding management. The system integrates an ESP32 microcontroller with DS18B20 temperature sensors, PH-4502C pH sensors, a DS3231 real-time clock, servo-based feeding mechanisms, and relay-controlled actuators for heating, cooling, and pH regulation. Sensor data is transmitted to a Firebase Realtime Database, enabling real-time monitoring and remote configuration via an Android app developed with MIT App Inventor. The main contribution of this work is the integration of real-time monitoring, automated environmental control, and configurable feeding management within a unified IoT architecture. Unlike previous studies that focused mainly on monitoring or single-parameter control, the proposed system introduces a time-based safety mechanism that uses the real-time clock (RTC) to prevent excessive pH correction. It also allows for the remote adjustment of feeding parameters through a cloud-based platform. The experimental results demonstrate that the system successfully maintains the water temperature within the range of 24–26 °C and the pH level between 6.5 and 7.5. This is achieved while executing scheduled feedings twice per day and ensuring reliable actuator performance. The system demonstrates stable operation with an average data transmission latency of approximately one second, indicating effective Internet of Things (IoT) communication. Overall, the smart aquarium system provides a practical, scalable, and user-friendly solution for managing aquariums intelligently, significantly reducing the need for manual intervention to maintain optimal environmental conditions for goldfish.